Statistical Approach for the Development of Tangential Cutting Force Model in End Milling Of Ti6Al4V - Patwari, Muhammed Anayet Ullah; A.K.M., Nurul Amin; Faris, Waleed Fekry (Trans Tech Publications, Switzerland, 2011)
Dynamic change in cutting force is one of the major causes of chatter formation in metal cutting which affect machining accuracy. Thus, accurate modeling of cutting force is necessary for the prediction of machining performance and determination of the mechanisms and machining parameters that affect the stability of machining operations. The present paper discusses the development of a mathematical model for predicting the tangential cutting force produced in endmilling operation of Ti6Al4V. The mathematical model for cutting force prediction has been developed in terms of the input cutting parameters cutting speed, feed rate, and axial depth of cut using response surface methodology (RSM). Effects of all the individual cutting parameters on cutting force as well as their interactions are investigated in this study. Central composite design was employed in developing the cutting force model in relation to the primary cutting parameters. The experimental results indicate that the proposed mathematical models suggested could adequately describe the performance indicators within the limits of the factors that are being investigated.